2013
DOI: 10.1111/rda.12225
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Levels of Glycerol and Cholesterol‐Loaded Cyclodextrin on Cryosurvival of Ram Spermatozoa

Abstract: This study was conducted to determine the optimum level of glycerol and cholesterol-loaded cyclodextrin (CLC) in a Tris-based diluent for cryopreservation of ram spermatozoa. Ram semen was treated with 0, 1.5, 3 or 4.5 mg CLC/120 × 10(6)  cells in Tris-based diluents containing 3, 5 or 7% glycerol in a factorial arrangement 3 × 4 and frozen in liquid nitrogen vapour. Sperm motility, viability (eosin-nigrosin staining) and functional membrane integrity (hypo-osmotic swelling test) were assessed immediately afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…Measuring cell volume changes, Glazar and colleagues showed that the addition of CDC complex in the extender increased the permeability of stallion spermatozoa to cryoprotectants [12]. Additionally, the CDC complex can form a protective sheath against water exchange [4] and can regulate the cholesterol content and thickness of membrane, which may help spermatozoa to tolerate volume changes [22]. Therefore our study confirms the protective role of cyclodextrincholesterol complex in a commercial extender for the freezing of sperm stallion.…”
Section: Discussionsupporting
confidence: 89%
“…Measuring cell volume changes, Glazar and colleagues showed that the addition of CDC complex in the extender increased the permeability of stallion spermatozoa to cryoprotectants [12]. Additionally, the CDC complex can form a protective sheath against water exchange [4] and can regulate the cholesterol content and thickness of membrane, which may help spermatozoa to tolerate volume changes [22]. Therefore our study confirms the protective role of cyclodextrincholesterol complex in a commercial extender for the freezing of sperm stallion.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, in two trials comparing methyl formamide (MF) and ethylene glycol (EG) with glycerol (G) it has been observed that glycerol gave more cryosurvival quality [44] than MF and EG additions [33], however, the nearest results to glycerol (5 %) were provided in the sample concentrated with EG 3 % (Table). On the other hand, the addition of 3 % glycerol ve 1.5 mg CLC/120½10 6 spermatozoa combination to freezing diluent was more amendatory compared to other groups, despite glycerol decreased the viability [45]. o t е.…”
mentioning
confidence: 86%
“…Some alternative substances have been tested, as alone or combined by, with/without various glycerol concentrations in extenders for improving freezability of ram semen [33,44,45].…”
mentioning
confidence: 99%
“…In Ram particularly, cyclodextrins-cholesterol complex has been reported to improve motility, viability and membrane integrity (Ahmad et al, 2013;Awad, 2011;Mocé et al, 2010;Motamedi-Mojdehi et al, 2014). Cyclodextrins are oligosaccharides with an internal hydrophobic cavity which forms inclusion complexes with various hydrophobic guest molecules, including cholesterol and lipophilic vitamins, and an external hydrophilic face increasing their solubility in semen extenders (Dodziuk, 2006;López-Nicolás et al, 2012).…”
Section: Introductionmentioning
confidence: 97%